Estrategias anestésicas en caninos y felinos durante la pasantía en un clínica veterinaria de Bogotá (2023)
In veterinary practice, anesthesia is an essential element, used in various medical situations, such as emergency surgeries, preventive surgeries, and diagnostic procedures